Experimental investigation of the night heat losses of hot water storage tanks in thermosyphon solar water heaters - Siamas, George A.; Roditis, George; Kyriacou, Paraskevas; Eleftheriou, Polyvios; Michaelides, Ioannis (My University, 2011)
The effects of night heat losses on the performance of thermosyphon solar water heaters have been experimentally examined. Three typical thermosyphon solar water heating systems with different storage tank sizes were tested by utilising the method suggested by ISO 9459-2:95. The results were analysed to quantify the night heat losses and to investigate the effect that these may have on the system daily performance. Analysis of the results showed that a linear behavior of the heat losses with the night mean ambient temperature exists. The correlation coefficients of the linearity, for the three systems under consideration, range from 0.93 to 0.97, with the losses reaching almost 8000 kJ at a mean ambient air temperature of 10 C. This value represents a significant percentage of the daily collected energy, making the night losses one of the most important sources of energy loss in thermosyphonic systems.
Keywords: Solar collectors; Solar water heaters; Tube solar